Enantioselective Phase‐Transfer Catalytic α‐Benzylation and α‐Allylation of α‐tert‐Butoxycarbonyllactones. Issue 4 (22nd February 2013) - Ha, Min Woo; Lee, Heejin; Yi, Hye Yeong; Park, Yohan; Kim, Sori; Hong, Suckchang; Lee, Myungmo; Kim, Mi‐hyun; Kim, Taek‐Soo; Park, Hyeung‐geun
Abstract A new enantioselective α‐benzylation and α‐allylation of α‐tert‐butoxycarbonyllactones was devloped. α‐Benzylation and α‐allylation of α‐tert‐butoxycarbonylbutyrolactone and α‐tert‐butoxycarbonylvalerolactone under phase‐transfer catalytic conditions (50% cesium hydroxide, toluene, −60 °C) in the presence of (S, S)‐3, 4, 5‐trifluorophenyl‐NAS bromide (1 mol%) afforded the corresponding α‐substituted α‐tert‐butoxycarbonyllactones in very high chemical yields (up to 99%) and optical yields (up to 99% ee). The synthetic potential of this method has been successfully demonstrated by the asymmetric synthesis of unnatural α‐quaternary homoserines, 3‐alkyl‐3‐carboxypyrrolidine and 3‐alkyl‐3‐carboxypiperidine.